2019
DOI: 10.1016/j.ijscr.2019.10.051
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic rupture of a non-parasitic simple hepatic cyst presenting as an acute surgical abdomen: Case report

Abstract: HighlightsTraumatic rupture of a non-parasitic simple hepatic cyst is very unusual.Open or laparoscopic cyst deroofing is a safe and effective treatment for non-parasitic simple hepatic cysts.Rupture of a non-parasitic simple hepatic cyst could be included in the differential diagnosis of acute abdomen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(24 citation statements)
references
References 18 publications
(49 reference statements)
0
24
0
Order By: Relevance
“…The evidence base on the rupture of hepatic cysts comes from a few case reports. [74][75][76][77][78] These studies reported a median cyst size (prior to rupture) of >10 cm (range 2-35 cm). Risk factors for cyst rupture include cyst haemorrhage, cyst infection, trauma and intervention.…”
Section: Recommendationsmentioning
confidence: 99%
“…The evidence base on the rupture of hepatic cysts comes from a few case reports. [74][75][76][77][78] These studies reported a median cyst size (prior to rupture) of >10 cm (range 2-35 cm). Risk factors for cyst rupture include cyst haemorrhage, cyst infection, trauma and intervention.…”
Section: Recommendationsmentioning
confidence: 99%
“…However, the recurrence rate of the cyst is >80% and is associated with further hemorrhage and subsequently the likelihood of acute abdomen and the need for emergent surgery [ 3 ]. It is also important to note that >50% of patients with hemorrhagic liver cysts present to the ED after a traumatic inciting event such as: massaging the cyst (our patient), pregnancy and recent abdominal contusion and/or ground level fall [ 1 , 3 , 5–7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Simple hepatic cysts, which are non-parasitic in nature, represent a prevalent form of benign liver ailment, affecting roughly 1–5 % of individuals within the general population [ 1 ]. Advancements in imaging technology have led to a rise in the inadvertent identification of these cysts through abdominal ultrasonography or computed tomography (CT) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…These cysts typically present as asymptomatic, permitting conservative follow-up without targeted intervention [ 1 , 3 ]. Nevertheless, certain cysts may be linked with complications including infection, hemorrhage, obstructive jaundice, portal hypertension, and rupture [ 1 , 4 ]. Exceptionally, it can be revealed by respiratory symptoms such as dyspnea [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation